A highly porous nanocomposite (Fe3O4@BFR) for the removal of toxic Cd(II) ions from aqueous environment: Adsorption modelling and regeneration study. (1st September 2019) - Naushad, Mu.; Ahamad, Tansir; Al-Ghanim, Khalid A.; Al-Muhtaseb, Ala'a H.; Eldesoky, Gaber E.; Khan, Azmat Ali
Abstract: Adsorption is a commonly used technique for the removal of pollutants from wastewaters. In this study, a magnetic adsorbent (Fe3 O4 @BFR) was prepared using biuret-formaldehyde pre polymeric resin (BFR) and Fe3 O4 nanoparticles. The adsorption ability of Fe3 O4 @BFR was investigated using Cd(II) metal ion as a typical pollutant. Adsorption of Cd(II) was studied as a function of temperature (25–45 °C), pH (2–7), time (5–300 min) and initial Cd(II) concentration (25–75 mg L −1 ). The morphology, structure and magnetic character of Fe3 O4 @BFR nanocomposite were explored using X-ray powder diffraction, Fourier transform infrared spectroscopy, N2 adsorption-desorption isotherm, scanning electron microscopy and VSM analyses. Adsorption kinetics, isotherms and thermodynamics studies were also carried out. The experimental adsorption data followed the pseudo-first-order kinetic model and Langmuir isotherm with a maximum adsorption capacity of 92.6 mg g −1 . The reusability of Fe3 O4 @BFR was tested and still over 70% Cd(II) was removed after three cycles. In conclusion, Fe3 O4 @BFR nanocomposite showed enormous potential for remediating industrial wastewater polluted by toxic Cd(II) metal ion. Highlights: Fe3 O4 @BFR was prepared using biuret-formaldehyde pre polymeric resin and Fe3 O4 nanoparticles. Fe3 O4 @BFR was used for the adsorptive removal of Cd(II) from aqueous medium. The process obeys Langmuir isotherm and pseudo first order kinetic model. The adsorption was increased with increasing the temperature.